Preparation method and application of anion exchange membrane with low water content and acid blocking function

By designing anion exchange membrane with low moisture content, using materials such as poly(vinylidene fluoride-co-hexafluoropropylene) and N-methyldiallylamine, the problem of poor acid resistance performance of traditional anion exchange membranes is solved, and higher acid recovery efficiency and better mechanical properties are achieved.

CN115888853BActive Publication Date: 2025-02-28ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211601943.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-13
Publication Date
2025-02-28
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

Traditional anion exchange membranes have poor acid resistance due to their high moisture content, which cannot improve the acid recovery concentration.

Method used

By designing an anion exchange membrane with low moisture content, using materials such as poly(vinylidene fluoride-co-hexafluoropropylene) and N-methyldiallylamine, the moisture content of the membrane is reduced and the acid resistance performance is improved through elimination reactions and grafting reactions.

Benefits of technology

The preparation of a low moisture content anion exchange membrane is achieved, which significantly improves the acid resistance performance and acid stability, enhances mechanical strength, and is suitable for the application of electrodialysis concentrated acids.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003995390610000071
    Figure BDA0003995390610000071
  • Figure BDA0003995390610000081
    Figure BDA0003995390610000081
  • Figure HDA0003995390620000011
    Figure HDA0003995390620000011
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of an anion exchange membrane with low water content and acid blocking function. The present invention provides application of the prepared anion exchange membrane in electrodialysis acid concentration. The preparation process of the present invention is simple, and good acid blocking performance is achieved by making the anion exchange membrane have a lower water content, and the acid stability and mechanical strength of the membrane are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of an anion exchange membrane and application of the anion exchange membrane in acid concentration. Background Art

[0002] In industrial production and life, a large amount of acidic wastewater is often produced. For example, in the metallurgical industry, a large amount of acid is needed for washing; in the production process of nitrocellulose, a large amount of acidic waste liquid is also produced. The most common method for treating acidic wastewater is to neutralize it with lime and then discharge it. This method not only causes serious waste of resources, but also causes secondary pollution to the environment. If the waste acid is recovered and concentrated by electrodialysis technology, resources will be saved to the maximum extent, and the whole process is environmentally friendly and meets the requirements of sustainable development.

[0003] Electrodialysis technology uses the potential difference as the driving force under the action of a DC electric field and utilizes the selective permeability of ion exchange membranes to separate electrolytes from solutions, thereby achieving the purpose of desalination, concentration, refinement, and purification of solutions. Due to its advantages such as simple operation, reliable operation, high efficiency, and small footprint, it is suitable for industrial water treatment projects of varying scales, such as seawater desalination, radioactive waste liquid treatment, acid and alkali preparation, and acid recovery.

[0004] At present, the research on ion exchange membranes, which are the "heart of electrodialysis", has attracted more and more attention. According to the different dissociable active charged groups on the polymer chain, they are divided into cation exchange membranes that are negatively charged and allow cations to pass through, and anion exchange membranes that are positively charged and allow anions to pass through. Anion exchange membranes for concentrated acid have attracted much attention due to their outstanding advantages in the field of waste acid recovery and treatment, such as high treatment efficiency, resource conservation and environmental friendliness. However, the research on anion exchange membranes for concentrated acid is still in its infancy. It is very difficult to require anion exchange membranes to have better acid resistance under the action of concentration gradient and excellent mechanical properties at the same time. In order to obtain excellent concentrated acid performance, predecessors have made a lot of efforts, but there are still problems such as poor concentration effect, poor membrane acid resistance and unclear factors affecting hydrogen ion leakage.

[0005] In summary, in order to solve the problem that traditional anion exchange membranes have poor acid resistance due to high water content and cannot increase the recovered acid concentration, an anion exchange membrane with low water content and good acid resistance is designed and developed to achieve higher acid recovery efficiency. Summary of the invention

[0006] In view of the above problems existing in the prior art, the present invention provides a method for preparing an anion exchange membrane with low water content and good acid resistance. The preparation process is simple, and good acid resistance is achieved by making the anion exchange membrane have a lower water content, and the acid stability and mechanical strength of the membrane are improved.

[0007] The second problem to be solved by the present invention is to provide application of the anion exchange membrane in acid concentration.

[0008] The technical solution adopted by the present invention is as follows:

[0009] In a first aspect, the present invention provides a method for preparing an anion exchange membrane having an acid-blocking function, comprising the following steps:

[0010] (1) dissolving a certain amount of poly(vinylidene fluoride-co-hexafluoropropylene) in N,N-dimethylacetamide, wherein 15 to 20 mL of N,N-dimethylacetamide is required per gram of poly(vinylidene fluoride-co-hexafluoropropylene), and stirring the mixture sufficiently at room temperature to obtain a transparent solution A;

[0011] (2) measuring a certain volume of 0.035-0.15 mol / L strong base alcohol solution and slowly adding it to the solution A obtained in step (1), wherein the volume ratio of solution A to 0.035-0.15 mol / L strong base alcohol solution is 10:1-20:1, and magnetically stirring at room temperature for 1-2 hours to obtain solution B;

[0012] (3) slowly pouring solution B into an excess of deionized water to obtain a fibrous solid, then washing the solid with deionized water until it is neutral, and vacuum drying at 60 to 80° C. for 24 to 48 hours to obtain a solid C;

[0013] (4) taking a sample of solid C, N-methyldiallylamine, and 2,2-azobisisobutyronitrile in a mass ratio of 1:0.2-0.5:0.01-0.02, and dissolving the sample in a certain amount of N-methylpyrrolidone to obtain a solution D;

[0014] (5) Solution D is heated to 60-90° C. in a nitrogen atmosphere and reacted for 8-12 h. The resulting solution is spread on a clean glass plate and vacuum dried at 60-90° C. for 12-24 h to obtain an anion exchange membrane with acid-blocking properties.

[0015] Preferably, the strong base is sodium hydroxide or potassium hydroxide.

[0016] Preferably, the alcohol in the strong alkaline alcohol solution is isopropanol.

[0017] Preferably, the thickness of the anion exchange membrane is controlled between 105 and 140 μm.

[0018] The room temperature described in the present invention is preferably between 20 and 30°C.

[0019] The invention firstly dissolves poly(vinylidene fluoride-co-hexafluoropropylene) in an organic solvent to prepare a polymer solution, and a strong alkaline alcohol solution can remove hydrogen fluoride from the poly(vinylidene fluoride-co-hexafluoropropylene) polymer solution through an elimination reaction to generate a carbon-carbon double bond with an active site; N-methyldiallylamine undergoes a grafting reaction with the active site of the poly(vinylidene fluoride-co-hexafluoropropylene) modified with a strong base in the presence of an initiator, and N-methyldiallylamine is protonated under acidic conditions, which is beneficial to the conduction of ions in the membrane, so that an anion exchange membrane with low water content and acid resistance is obtained.

[0020] In a second aspect, the present invention provides the use of the anion exchange membrane in electrodialysis acid concentration.

[0021] Before use, the low-water-content anion exchange membrane with acid-blocking performance prepared by the present invention needs to be soaked in an acid aqueous solution for a certain period of time, such as being fully soaked in a dilute sulfuric acid solution (such as soaking for 12 hours).

[0022] Compared with existing materials and technologies, the present invention has the following advantages:

[0023] 1) The anion exchange membrane prepared by the preparation method proposed in the present invention has low water content and excellent acid resistance, can effectively reduce the leakage of hydrogen ions, and is suitable for electrodialysis acid concentration.

[0024] 2) The anion exchange membrane prepared by the present invention has good acid resistance and low mass loss rate after long-term strong acid immersion.

[0025] 3) The anion exchange membrane prepared by the present invention has a simple preparation process, simple synthesis steps, and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of an electrodialysis acid concentration device used in an embodiment of the present invention. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme will be further described clearly and completely by examples below. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0028] The low-water content anion exchange membrane prepared by the method of the present invention has good acid concentration performance, and the leakage process of hydrogen ions is hindered by reducing the water content of the ion exchange membrane, thereby increasing the concentrated acid concentration, and the preparation method is simple.

[0029] The samples involved are as follows: Poly(vinylidene fluoride-co-hexafluoropropylene): Sigma-Aldrich Corporation, USA; N,N-dimethylacetamide, 99.5%, Anergy Chemical; Sodium hydroxide (granular), Sinopharm Chemical Reagent Co., Ltd.; Potassium hydroxide, Hangzhou Xiaoshan Chemical Reagent Factory; Isopropanol, 99.7%, Shanghai Titan Chemical Co., Ltd.; N-methyldiallylamine, Shanghai Aladdin Biochemical Technology Co., Ltd.; 2,2-Azobisisobutyronitrile, 98%, Shanghai Aladdin Biochemical Technology Co., Ltd.; N-Methylpyrrolidone, 99.0%, Shanghai Titan Chemical Co., Ltd.

[0030] The room temperature described in the embodiment of the present invention is about 25°C.

[0031] Example 1

[0032] (1) Weigh 20 g of poly(vinylidene fluoride-co-hexafluoropropylene) in a single-necked flask, dissolve it in 300 mL of N,N-dimethylacetamide, wherein 15 mL of N,N-dimethylacetamide is required for each gram of poly(vinylidene fluoride-co-hexafluoropropylene), and stir at room temperature for 10 h to obtain a transparent solution A;

[0033] (2) According to the volume ratio of solution A to 0.15 mol / L sodium hydroxide isopropanol solution of 10:1, 30 mL of sodium hydroxide alcohol solution was measured and slowly added to 300 mL of solution A, and magnetically stirred at room temperature for 1 h to obtain solution B;

[0034] (3) Solution B was slowly added to an excess of deionized water to obtain a brown-red fibrous solid. The solid was then washed with deionized water until neutral, and vacuum dried at 60°C for 24 hours to obtain solid C;

[0035] (4) Weigh 2 g of solid C, 0.4 g of N-methyldiallylamine, and 0.02 g of 2,2-azobisisobutyronitrile, and dissolve them in 30 mL of N-methylpyrrolidone to obtain solution D;

[0036] (5) Solution D was heated to 70°C in an oil bath in a nitrogen atmosphere. After reacting for 12 hours, the solution was spread on a clean glass plate and vacuum dried at 80°C for 12 hours to obtain an anion exchange membrane with a low water content and acid resistance and a thickness of 121 μm. This membrane was designated as AEM-1.

[0037] Example 2

[0038] (1) Weigh 10 g of poly(vinylidene fluoride-co-hexafluoropropylene) in a single-necked flask, dissolve it in 150 mL of N,N-dimethylacetamide, where 15 mL of N,N-dimethylacetamide is required for each gram of poly(vinylidene fluoride-co-hexafluoropropylene), and stir at room temperature for 10 h to obtain a transparent solution A;

[0039] (2) 15 mL of sodium hydroxide alcohol solution was slowly added to 150 mL of solution A at a volume ratio of solution A to 0.15 mol / L sodium hydroxide isopropanol solution of 10:1, and the mixture was magnetically stirred at room temperature for 1.5 h to obtain solution B;

[0040] (3) Solution B was slowly added to an excess of deionized water to obtain a brown-red fibrous solid. The solid was then washed with deionized water until neutral, and vacuum dried at 60°C for 24 hours to obtain solid C;

[0041] (4) Weigh 2 g of solid C, 0.6 g of N-methyldiallylamine, and 0.02 g of 2,2-azobisisobutyronitrile, and dissolve them in 30 mL of N-methylpyrrolidone to obtain solution D;

[0042] (5) Solution D was heated to 70°C in an oil bath in a nitrogen atmosphere. After reacting for 12 hours, the solution was spread on a clean glass plate and vacuum dried at 80°C for 12 hours to obtain an anion exchange membrane with a low water content and acid resistance performance and a thickness of 126 μm. This was recorded as AEM-2.

[0043] Example 3

[0044] (1) Weigh 10 g of poly(vinylidene fluoride-co-hexafluoropropylene) in a single-necked flask, dissolve it in 150 mL of N,N-dimethylacetamide, where 15 mL of N,N-dimethylacetamide is required for each gram of poly(vinylidene fluoride-co-hexafluoropropylene), and stir at room temperature for 10 h to obtain a transparent solution A;

[0045] (2) 10 mL of sodium hydroxide alcohol solution was slowly added to 100 mL of solution A at a volume ratio of solution A to 0.15 mol / L sodium hydroxide alcohol solution of 10:1, and magnetically stirred at room temperature for 2 h to obtain solution B;

[0046] (3) Solution B was slowly added to an excess of deionized water to obtain a brown-red fibrous solid. The solid was then washed with deionized water until neutral, and vacuum dried at 60°C for 24 hours to obtain solid C;

[0047] (4) Weigh 2 g of solid C, 0.8 g of N-methyldiallylamine, and 0.02 g of 2,2-azobisisobutyronitrile, and dissolve them in 30 mL of N-methylpyrrolidone to obtain solution D;

[0048] (5) Solution D was heated to 80°C in an oil bath in a nitrogen atmosphere. After reacting for 12 hours, the solution was spread on a clean glass plate and vacuum dried at 80°C for 12 hours to obtain an anion exchange membrane with a low water content and acid resistance performance and a thickness of 131 μm. This was recorded as AEM-3.

[0049] The performance of the prepared anion exchange membrane was tested as follows:

[0050] Test 1: The membrane thickness, membrane surface resistance and ion exchange capacity data are shown in Table 1.

[0051] Table 1 Types and properties of ion exchange membranes used

[0052] Membrane Type Thickness(μm) <![CDATA[Sheet Resistance (Ω·cm 2 )]]> <![CDATA[Ion exchange capacity (mmol·g –1 )]]> CEM-Type-II 122 3.53 1.35 AMX 120 4.56 1.22 AEM-1 121 4.23 1.23 AEM-2 126 2.35 1.33 AEM-3 131 2.82 1.28

[0053] Test 2: In order to evaluate the acid concentration performance of the prepared anion exchange membrane, the current density (I = 20 mA cm -2 ) was used to conduct an electrochemical experiment of H2SO4 concentration. Before use, the prepared anion exchange membrane was soaked in a 0.5 mol / L dilute sulfuric acid solution for 12 hours. Figure 1 As shown in FIG. 1 , a stack consisting of a concentrated / diluted electrode chamber (CC / DC) and two cells with ruthenium-coated titanium electrodes was used. In the ED device, the effective area of ​​the prepared AEM was 7.065 cm 2 The cation exchange membrane CEM used in the ED device is the CEM-Type-II cation exchange membrane produced by Fuji Corporation of Japan, and the anion exchange membrane used as the control group is the AMX anion exchange membrane produced by Astom Corporation of Japan. The initial H2SO4 concentrations of CC and DC were both 0.5 M. Considering the water migration caused by the concentration difference during the entire experiment, the initial volumes of the H2SO4 solutions in DC and CC were 250 mL and 15 mL, respectively. In addition, the H2SO4 solution in DC was circulated at a speed of 60 rpm using a peristaltic pump. The concentration process was carried out at a current density of 20 mA cm -2 The concentration of H2SO4 in CC and DC was determined by acid-base neutralization titration. The final volume of H2SO4 solution in CC and DC was accurately recorded. + Concentration (mol / L), the results are shown in Table 2.

[0054] Table 2 H in the acid concentration system at different time periods + Concentration of the concentrator

[0055] Time (h) 0 1 3 6 9 12 <![CDATA[H of Example 1 + Concentration (mol / L)]]> 0.98 1.21 1.42 1.67 1.83 2.21 <![CDATA[H of Example 2 + Concentration (mol / L)]]> 0.98 1.35 1.54 1.70 1.99 2.35 <![CDATA[H of Example 3 + Concentration (mol / L)]]> 0.98 1.42 1.54 1.65 1.79 1.97

[0056] Test 3: The chemical stability of the prepared anion exchange membrane in H2SO4 solution was tested, and the chemical stability of the anion exchange membrane before and after being used for sulfuric acid enrichment in ED was investigated. The weight loss rate was used as an indicator, and the weight difference was used as an indicator to evaluate its chemical stability. After being completely dried in a vacuum drying oven at 80°C for 24 hours, the weight of the sample was recorded. Then, the dried ion exchange membrane sample was soaked in a 2.0M H2SO4 solution at 80°C for 1h, 6h, 12h, 24h, 32h, and 48h, and then the retained solution on the surface of the sample was carefully wiped, and the soaked membrane was washed with water until the water became neutral. Then, the ion exchange membrane sample was dried under vacuum conditions at 80°C for 24h, and then the membrane mass was re-weighed, and the mass loss was used to characterize the acid resistance. The results are shown in Table 3.

[0057] Table 3 Weight loss rate of immersion in 2.0 mol / L sulfuric acid solution for different time periods

[0058] Time (h) 1 6 12 24 32 48 AEM-1 weight loss rate (%) 0.79±0.03 0.83±0.02 0.84±0.01 0.83±0.02 0.84±0.01 0.85±0.02 AEM-2 weight loss rate (%) 0.90±0.03 0.90±0.04 0.91±0.02 0.92±0.01 0.93±0.01 0.91±0.02 AEM-3 weight loss rate (%) 0.90±0.03 0.91±0.02 0.90±0.02 0.91±0.02 0.92±0.02 0.90±0.02

[0059] Test 4: Compare the moisture content of the prepared anion exchange membrane with that of the traditional quaternary ammonium membrane AMX at different temperatures. After the tested membrane sample is completely dried in a vacuum drying oven at 80°C for 24 hours, the length of the membrane sample is recorded. Then, the dried ion exchange membrane sample is soaked in deionized water at 20°C, 30°C, and 40°C for 48 hours. Then, the residual solution on the surface of the sample is carefully wiped off, and the mass of the membrane sample is recorded. Calculate the moisture content compared to the mass of the sample in the dry state. The results are shown in Table 4.

[0060] Table 4 Water content of samples and AMX at different temperatures

[0061]

[0062]

[0063] The present invention is specifically demonstrated and introduced through the above-mentioned preferred embodiments, but those skilled in the art should understand that various changes can be made to the present invention in form and details without departing from the spirit and scope of the present invention as defined in the appended claims, all of which are within the scope of protection of the present invention.

Claims

1. A method for preparing an anion exchange membrane with acid-blocking function, characterized in that: The preparation method comprises the following steps: (1) dissolving a certain amount of poly(vinylidene fluoride-co-hexafluoropropylene) in N,N-dimethylacetamide, wherein 15 to 20 mL of N,N-dimethylacetamide is required per gram of poly(vinylidene fluoride-co-hexafluoropropylene), and stirring the mixture sufficiently at room temperature to obtain a transparent solution A; (2) measuring a certain volume of 0.035-0.15 mol / L strong base alcohol solution and slowly adding it to the solution A obtained in step (1), wherein the volume ratio of solution A to 0.035-0.15 mol / L strong base alcohol solution is 10:1-20:1, and magnetically stirring at room temperature for 1-2 hours to obtain solution B; (3) slowly pouring solution B into an excess of deionized water to obtain a fibrous solid, then washing the solid with deionized water until it is neutral, and vacuum drying at 60 to 80° C. for 24 to 48 hours to obtain a solid C; (4) taking a sample of solid C, N-methyldiallylamine, and 2,2-azobisisobutyronitrile in a mass ratio of 1:0.2-0.5:0.01-0.02, and dissolving the sample in a certain amount of N-methylpyrrolidone to obtain a solution D; (5) Solution D is heated to 60-90° C. in a nitrogen atmosphere and reacted for 8-12 h. The resulting solution is spread on a clean glass plate and vacuum dried at 60-90° C. for 12-24 h to obtain an anion exchange membrane with acid-blocking properties.

2. The preparation method according to claim 1, characterized in that: The strong base is sodium hydroxide or potassium hydroxide.

3. The preparation method according to claim 1 or 2, characterized in that: The alcohol in the strong alkaline alcohol solution is isopropanol.

4. The preparation method according to claim 1, characterized in that: The room temperature is between 20 and 30°C.

5. The preparation method according to claim 1, characterized in that: The thickness of the anion exchange membrane is controlled between 105 and 140 μm.

6. Use of the anion exchange membrane prepared according to the preparation method of claim 1 in electrodialysis acid concentration.

7. The use according to claim 6, characterized in that: The anion exchange membrane with acid-blocking performance is fully soaked in an acid aqueous solution before use.

Citation Information

Patent Citations

  • Anion exchange membrane with acid blocking function and preparation method thereof

    CN105617891A

  • Preparation method of modified poly (vinylidene fluoride-co-hexafluoropropylene) grafted vinyl imidazole anion exchange membrane

    CN113667161A